PENGARUH PELAKSANAAN ETIKA PROFESI DAN KECERDASAN EMOSIONAL TERHADAP PENGAMBILAN KEPUTUSAN BAGI AUDITOR - Arma Mulawaty Ramadhan; Masriani Mahyuddin; Hadriana Hanafie (J-MACC, 2024)
In the business world, auditors are often considered to be deviating from moral activity because their ethics and obligations as professionals are not implemented properly. The role and responsibility of the auditor to the public interest is really the basis for the existence of the profession of auditor. The ethics of the profession has a significant influence on decision-making for the auditor. In addition to ethics in the profession, an accountant is also required to have good emotional intelligence. Emotional intelligence (EQ) is the ability of a person to regulate his or her emotional life, maintain emotional alignment and expression through self-awareness skills, self-control, self motivation, empathy and social skills. The study aims to test and analyse evidence on the influence of professional ethics and emotional intelligence on decision-making for auditors. This research uses a survey method using primary data obtained from the questionnaire. The population in this study is the entire auditor who works at the office of the Financial Supervisory Authority and Development of the South Sulawesi Representative. The sample in the study consisted of 61 auditors consisting of 32 male and 29 female respondents. Analysis of research data using double linear regression analysis with SPSS program version 26. The results of this study show that professional ethics has a positive and significant influence on decision-making for auditors, emotional intelligence has a negative and significant impact on decision making for auditors.